Antimicrobial Activity of N-ariliden(alkylidene)hydrazides of Carboxymethylalginic Acid - D. N. Kosareva; E. P. Ananieva; A. A. Iozep (Разработка и регистрация лекарственных средств, 2019)
Introduction. Nowadays, due to the emergence of new broad-spectrum antibiotics and synthetic chemotherapeutic agents, the use of nitrofuran has significantly decreased. At the same time, they remain important for the treatment of urinary tract infections and intestinal infections, as well as local antiseptics. However, low solubility in water, the possibility of undesirable reactions, as well as the absence of prolonged action significantly limit their use. It is known that the inclusion of biologically active substances in the polysaccharide molecule allows improving the already known drugs while changing their properties. Thus, the introduction of the 5-nitrofuran cycle in native alginic acid and some of its derivatives led to the emergence of antifungal activity and improved solubility. However, the information about the antimicrobial activity of N-arylidene(alkyliden)hydrazides of carboxymethylalginic acid in the literature are practically absent.Aim. Synthesis and study of antimicrobial activity of N-arylidene(alkyliden)hydrazides of carboxymethylalginic acid with different content of a biologically active fragment.Materials and methods. For the proof of the structure of the synthesized substances were used IR- and UV-spectroscopy, antimicrobial activity was analyzed by double serial dilution on the test-cultures Staphylococcus aureus, Escherichia coli and Candida albicans.Results and discussion. With the introduction of 5-nitrofurfural and β-(5-nitro-2-furyl)-acrolein into the carboxymethylalginic acid, samples with antimicrobial activity were obtained, whose spectrum of action differs from furacilin. Thus, in the polymer acylhydrazones β-(5-nitro-2-furyl)-acrolein of alginic acid, a high antifungal action against C. albicans was found, the fungistatic and fungicidal action reaches 1,8 and 3,6 µg/ml.Conclusion. The synthesized samples of polymer acylhydrazones 5-nitrofurfural and β-(5-nitro-2-furyl)-acrolein have antimicrobial action, and unlike furacilin are highly soluble in water and do not irritate the skin and mucous membranes. The content of 5-nitrofuran fragment, at which the maximum antimicrobial activity is achieved, is revealed.